Association of uterine rupture with pregestational diabetes in women undergoing trial of labor after cesarean delivery. (17th August 2020) - McLaren, Rodney A.; Ndubizu, Chima; Atallah, Fouad; Minkoff, Howard
Abstract: Objective: To evaluate the association of pregestational diabetes with uterine rupture during a trial of labor with one prior cesarean delivery. Study design: A retrospective study of women undergoing a trial of labor after cesarean. The study group consisted of women with pregestational diabetes and the control group was women without pregestational diabetes. Primary outcome was a uterine rupture. Data were extracted from the USA. Natality Database from 2012 to 2016. Maternal and neonatal outcomes were analyzed. Multivariable logistic regression analysis was used to estimate risks of uterine rupture and maternal and neonatal outcomes. Results: There were 359, 504 women undergoing labor after cesarean, with 3508 women with pregestational diabetes and 355, 996 without. The prevalence of uterine rupture among women with pregestational diabetes undergoing labor after cesarean was 0.5%, while among women without pregestational diabetes, it was 0.2% (adjusted odds ratio [OR] 2.03 [95% CI 1.18–3.51]; p = .01). There was an increased risk of unplanned hysterectomy among pregnancies complicated by pregestational diabetes (adjusted OR 3.06 [95% CI 1.41–6.66]). Conclusion: Women undergoing a trial of labor, who have pregestational diabetes had a higher rate of uterine rupture than women without a history of pregestational diabetes.